2010
DOI: 10.1159/000321387
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 3 Polymorphism rs3775291 Is Not Associated with Choroidal Neovascularization or Polypoidal Choroidal Vasculopathy in Chinese Subjects

Abstract: Background/Aims: Age-related macular degeneration (AMD) is a leading cause of visual impairment. A single-nucleotide polymorphism (SNP; rs3775291) in the Toll-like receptor 3 (TLR3) gene has recently been implicated in the pathogenesis of AMD in Caucasian populations. The aim of this study was to examine this association in Chinese persons with choroidal neovascularization (CNV) secondary to AMD and polypoidal choroidal vasculopathy (PCV). Methods: This was an observational cross-sectional study in Singapore. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 73 publications
(43 reference statements)
1
15
0
Order By: Relevance
“…In our age-and gender-adjusted analysis, we provide new data that the TLR3 gene variant is not associated with either nAMD or PCV in Chinese. This is consistent with Sng et al (2011) and Zhou et al (2011), who proposed that the TLR3 mutation reduces binding capacity to dsRNA, protecting against GA rather than the neovascular phenotype. Moreover, genes that have been implicated in the pathogenesis of nAMD and PCV are usually factors likely involved in ischemia, inflammation, and local synthesis and secretion of angiogenic factors (Swaroop et al, 2007;Veritti et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our age-and gender-adjusted analysis, we provide new data that the TLR3 gene variant is not associated with either nAMD or PCV in Chinese. This is consistent with Sng et al (2011) and Zhou et al (2011), who proposed that the TLR3 mutation reduces binding capacity to dsRNA, protecting against GA rather than the neovascular phenotype. Moreover, genes that have been implicated in the pathogenesis of nAMD and PCV are usually factors likely involved in ischemia, inflammation, and local synthesis and secretion of angiogenic factors (Swaroop et al, 2007;Veritti et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…This could have led to a fallacious association because AMD is strongly age-related. Other studies with primarily Caucasian subjects, adjusted for age and gender, did not detect an association between the rs3775291 SNP and either GA or neovascular AMD (Edwards et al, 2008;Allikmets et al, 2009;Cho et al, 2009b) Furthermore, Sng et al (2011) found that the TLR3 polymorphism rs3775291 was not associated with nAMD or PCV in Chinese. Thus, it remains uncertain if TLR3 is associated with nAMD or PCV.…”
Section: Discussionmentioning
confidence: 90%
“…Genes in the collagen matrix pathway, COL10A1 and COL8A1 [24], the extracellular matrix pathway, TIMP3 [24,37], the angiogenesis pathway, VEGF [3,24], also show association with AMD. Other genes, such as those involved with inflammation and immunity, TLR3 [61] and SOD2 [62], and the 9p21 region [63] did not show an association with AMD. In recent years, meta-analyses demonstrated that the REST-C4orf14-POLR2B-IGFBP7 at 4q21 does not show an association with AMD, while the T allele at rs13278062 of TNFRSF10A-LOC389641 at 8p21 decreases risk of AMD [26,64] ( Table 1 ).…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…Due to a strong linkage disequilibrium across this region, it is difficult to genetically distinguish between these two susceptible candidates and prioritize of their importance toward disease pathogenesis [99]. Other studies have also examined the association of C2/CFB [90,92,96,100], SERPING1 [101,102], ELN [103-105], PEDF [106-108], APOE [59], SOD2 [62], TLR3 [61], the 9p21 region [63], RDBP [100], SKIV2L [100], and C3 [98] with PCV in different ethnicities, but meta-analysis shows that the results of these associations are inconclusive and sometimes underpowered [94]. A recent study demonstrated that REST-C4orf14-POLR2B-IGFBP7 at 4q21 did not show an association with PCV; however, the T allele at rs13278062 of TNFRSF10ALOC389641 at 8p21 decreases risk of PCV.…”
Section: Polypoidal Choroidal Vasculopathymentioning
confidence: 99%
“…64 Another study focusing on a separate group of Singaporean Chinese indicated that the TLR3 rs3775291 is not associated with CNV and polypoidal choridal vasculopathy (PCV), a condition similar to but distinct from AMD. 65 …”
Section: Distinct Amd Loci In Ethnic Groupsmentioning
confidence: 99%